Improving Students’ Conceptual Mastery on Digital Circuit Topic Using Electronics Workbench Software - Islahudin Islahudin; Soeharto Soeharto (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
This study aims at improving the comprehension of digital circuit’s concept by utilizing the electronic workbench software on the students of Physics Education Program, Muhammadiyah University of Mataram. The numbers of samples were 14 students who took Basic Electronics II course. The research design was Classroom Action Research. The study was conducted in two cycles. Each cycle consists of four stages of activity, namely Planning, Acting, Observing, and Reflecting. Technique of data analysis to determine the improvement of concept mastery in cycle 1 and cycle 2 was using the t-test formula. The results of data analysis obtained the classical passing grade in cycle 1 was 57.14 % and cycle 2 was 85.71%, so that the action was completed in cycle 2. The improvement in learning outcomes was included in the significant category because the t-test on the average of cycle 1 and cycle 2 showed the value of t calculation (= 2.41297)> t distribution (= 2.145) so that H0 < Ha. Based on the results of this study it can be concluded that the use of electronics workbench software can improve the mastery of digital circuit’s concept on the students of Physics Education Program, Muhammadiyah University of Mataram.